Implementing the 2020–2025 Dietary Guidelines for Americans: Recommendations for a path forward. Issue 12 (7th December 2021) - Sanders, Lisa M.; Allen, Jonathan C.; Blankenship, Jeanne; Decker, Eric A.; Christ‐Erwin, Mary; Hentges, Eric J.; Jones, Julie M.; Mohamedshah, Farida Y.; Ohlhorst, Sarah D.; Ruff, John; Wegner, Jill
Abstract : Abstract: The Dietary Guidelines for Americans (DGA) provide science‐based recommendations for healthy dietary patterns to promote health and reduce risk of chronic diseases. Yet, since their inception in 1980 and updates every 5 years, Americans fall short of meeting dietary recommendations and diet‐related chronic diseases continue to be a public health concern. In May of 2021, the Institute of Food Technologists and the Department of Food Science at the University of Massachusetts, Amherst, convened a diverse group of thought leaders in health, nutrition, and food science to identify opportunities and approaches to improve consumer adoption of the DGA recommendations. The invited leaders collaborated in roundtable discussions to develop recommendations and strategies to promote adoption of the DGA recommendations after hearing sessions on the latest consumer trends, advances in food science and technology, and effective communications approaches. Participants agreed that changes in consumer behaviors and heightened interest in health due to the novel coronavirus pandemic have created an opportune time to engage consumers about healthy eating. Communications must be simple, tailored to the consumer, and delivered by influencer(s)/spokesperson(s) who are credible sources and share personal values. Innovations in food science and technology have enabled improvements in the safety, health, acceptability, affordability, and availability of foods but opportunities to provide more options to enhance consumption of desired food groups, such as fruits, vegetables, and whole grains, remain. Moving Americans toward healthier dietary patterns aligned with DGA recommendations will require collaborations within the food sector and beyond to achieve broad scale amplification and investment.